NEW PRODUCT LAUNCH – CASE STUDY (Research Bulletins of the Faculty of Economic Sciences, 2025)
The aim of this article is to present methods for evaluating new product projects in the product development process. A literature analysis method is used and a Gantt chart is proposed for evaluating new product introduction projects. The paper presents a product life cycle and an analysis of the wine market in Malta. The time for the introduction of two types of wine was set at one year.
Keywords: product management, product life cycle (PLC), Gantt chart